(untitled) (Journal of Economic Research & Business Administration, 2018)
Contemporary challenges facing modern organization force its management to deal with changes, projects, innovations or start-ups. To maintain competitive advantages, it is important to develop skills necessary to solve emerging problems. The paper aims to discuss these issues. The authors have attempted to reveal leadership skills that are primarily needed to manage organizations effectively. This study applies the significance of soft skills. This study also identifies what skills should be perceived as soft ones. The purpose of scientific research is to study the degree of awareness concerning the soft skills concept among Kazakhstani employees. The theory of leadership generalizes the practical experience of hundreds and thousands of people. Without a theoretical foundation, it is difficult to develop leadership skills that are in demand today. Modern organizations to improve their effectiveness should focus on developing leadership skills, in particular soft skills, which are a reflection of the organization’s culture and strategy. Training of personnel, raising its awareness and implementing a program of leadership effectiveness are further directions of the research. Due to the selected survey approach the data are correlational and can be perceived as reliable but exploratory one. Thus, representative experimental data is needed to confirm the findings. A cross-sectional survey design with an n=155 employed people working for various organizations was selected. The research consisted of two stages. The first stage of the research was conducted on the base of exploratory research design. Secondary data presented in the literature review helped to propose two hypotheses. The comprehensive analysis of secondary data helped to interpret primary data with more insight. The initial prediction was that that low awareness leads to poor performance of any activity where people interact. Findings taken from online survey showed that the most Kazakhstani respondents (83%) are not informed about soft skills and as a result pay less attention to enhance them. The presented results present an important step toward understanding how Kazakhstani employees could increase the personal performance via increasing awareness of soft skills. Within the paper, the discussion focuses on the importance to increase awareness on the soft skills among Kazakhstani entrepreneurs, businesspersons and employees to expand boundaries of career opportunities.